2020
DOI: 10.7759/cureus.9812
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approved Biologics: Can Etanercept and Ustekinumab be Considered a First-Line Systemic Therapy for Pediatric/Adolescents in Moderate to Severe Psoriasis? A Systematic Review

Abstract: Psoriasis is a chronic immune-mediated skin disorder. Due to lack of clarity in its pathogenesis, a cure with existing treatment is a big challenge. Biologics, a revolutionary treatment, are potent immunomodulators that explicitly target the culprit cells of the immune system to achieve the maximum level of Psoriasis Area and Severity Index (PASI) score (75 to 90) and clear or almost clear skin in moderate to severe psoriasis. They have been a successful therapy in adult severe psoriasis for a decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These therapeutics have gained popularity in the treatment of psoriasis and are a mainstay of treatment. Currently, there are 11 FDA-approved biologics to treat psoriasis targeting the important TNF-α/IL-23/IL-17 inflammatory axis [ 52 ]. The four main classes are TNF-α inhibitors, IL-12/IL-23 inhibitors, IL-17 inhibitors, and IL-23/IL-39 inhibitors ( Figure 1 ) [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…These therapeutics have gained popularity in the treatment of psoriasis and are a mainstay of treatment. Currently, there are 11 FDA-approved biologics to treat psoriasis targeting the important TNF-α/IL-23/IL-17 inflammatory axis [ 52 ]. The four main classes are TNF-α inhibitors, IL-12/IL-23 inhibitors, IL-17 inhibitors, and IL-23/IL-39 inhibitors ( Figure 1 ) [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, dermatologists in support of using systemic treatments in paediatric PsO tended to be younger, work in hospitals and consult frequently with severe patients ( 29 ). Biologic therapies have been used to treat paediatric PsO for over a decade; data on the use of biologic therapy is quickly expanding and numerous studies have reported the safety of systemic therapy in this patient population ( 6 , 30 , 31 ). Nevertheless, the most common reasons for patients not receiving a biologic were patient/guardian decision and concerns regarding the safety/side-effect profile of biologic therapy, suggesting the need for better education surrounding the use of biologics for paediatric PsO patients and their parents/guardians.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitors of TNFα such as infliximab, etanercept, adalimumab are now second line to methotrexate in Rheumatoid arthritis, 13 while etanercept is first line treatment for psoriatic in children. 14 Other first line treatments include; the inhibitors of the vascular endothelial growth factor A (VEGF-A) such as bevacizumab, cetuximab, and panitumumab for metastatic colorectal cancer, 15 the inhibitors of the HER-2 such as trastuzumab for hormone sensitive metastatic breast cancer, 16 and the granulocyte colony stimulating factors such as filgrastim for chemotherapy induced neutropenia. 17 This is driven by clinical observations that, for most of these chronic disorders, particularly rheumatoid arthritis, early start of aggressive therapy with effective drugs and continuation of such therapy led to improved patient functionality and quality of life, and reduced comorbidities and increased survival.…”
Section: Discussionmentioning
confidence: 99%